The contemporary condition: Introductory thoughts on contemporaneity & contemporary art - Cox, Geoff; Lund, Jacob (The contemporary condition, 2016)
What do we mean when we say that something is contemporary? And what should the designator "contemporary art" refer to? An immediate response would be that contemporary art is an art of the present, that it somehow addresses and expresses the present. But what is this present? What constitutes the present present or the contemporary contemporary? This first book in the Contemporary Condition series introduces some of the key issues concerning contemporaneity as a defining condition of our historical present. It thus acts as an extended preface to the series as a whole, calling for a rethinking of the deep structures of temporalization that render our present the way it is.l